Pengaruh Investasi, Ekspor, Impor, Utang, Kurs, dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia Tahun 1994-2024 - Lola Aritasari; Firdayetti Firdayetti (Institut Manajemen Wiyata Indonesia, 2026)
This study analyzes the effects of investment, exports, imports, external debt, exchange rates, and inflation on Indonesia’s gross domestic product (GDP) using annual time-series data for the period 1994–2024 obtained from the World Bank. A dynamic econometric framework based on the Autoregressive Distributed Lag (ARDL) model is employed to capture both short-run dynamics and long-run relationships among the variables. The empirical results indicate that, in the short run, investment, exports, imports, external debt, and inflation have positive and statistically significant effects on GDP. In the long run, investment and external debt exert a positive and statistically significant impact on economic growth, whereas inflation has a negative and statistically significant effect, highlighting its adverse implications for macroeconomic stability. These findings suggest that sustaining economic growth in Indonesia requires policies that promote a conducive investment climate, ensure prudent external debt management, maintain fiscal discipline, and strengthen inflation stabilization efforts.